IDDF2022-ABS-0162 Histological remission using a nancy index of 0 is associated with longer relapse-free survival than histological activity in patients with ulcerative colitis in clinical and endoscopic remission. (2nd September 2022) - Pudipeddi, Aviv; Fung, Caroline; Kariyawasam, Viraj; Paramsothy, Ramesh; Ghaly, Simon; Haifer, Craig; An, Yoon; Begun, Jakob; Connor, Susan; Chetwood, John; Paramsothy, Sudarshan; Leong, Rupert
Abstract : Background: Current treatment guidelines recommend achieving clinical and endoscopic remission for patients with ulcerative colitis (UC). However, histological remission is evolving as an important treatment target in UC. We aimed to evaluate histological activity as a predictor for clinical relapse in vedolizumab-treated patients in both clinical and endoscopic remission. Methods: We report an interim exploratory analysis of a multi-centre randomised controlled trial [Vedolizumab Immunomodulator Enforced Withdrawal Study (VIEWS)]. UC patients in clinical remission (partial Mayo score ≤ 2 with no subscore > 1) and endoscopic remission (Mayo endoscopic subscore ≤ 1) were included. Histological remission was defined as a Nancy index (NI) of 0 (exploratory analysis of NI ≤ 1 also occurred). Kaplan-Meier analysis and Cox proportional hazard models were performed (HR and 95%CI). Results: There were 54 patients included. The median age was 44.0 years (IQR: 27.0–60.5) and the median follow-up time was 22.0 months (IQR: 13.5–29.5). Clinical relapse rates for patients with histological activity (NI ≥ 1) versus histological remission (NI=0) were 50.0% (n=5/10) versus 12.2% (n=5/41) respectively ( P =0.005). Patients in histological remission had significantly longer relapse-free survival compared with patients with histological activity ( P =0.004, IDDF2022-ABS-0162 Figure 1A. Kaplan-Meier curves demonstrating relapse-free survival rates stratified by histological remission defined as NI = 0). There was no significant difference in relapse-free survival when using a cutoff of NI ≤ 1 for histological remission ( P =0.69, IDDF2022-ABS-0162 Figure 1B. Kaplan-Meier curves demonstrating relapse-free survival rates stratified by histological remission defined as NI ≤ 1). On multivariate analysis, only histological activity was predicted for clinical relapse (aHR: 6.8, 95%CI: 1.5–30.1, P =0.01). Conclusions: Histological remission is associated with longer relapse-free survival than histological activity for UC patients in clinical and endoscopic remission. A NI score of 0 better predicted for relapse-free survival than NI ≤ 1. This is one of the first prospective studies examining the role of histology and long-term outcomes in UC.